PRIORITY LOADING ALGORITHM AS THE PART OF AIRCRAFT LOAD OPTIMIZATION MODEL - Sahun, Yelizaveta (Proceedings of National Aviation University, 2020)
Purpose: development of a new load optimization algorithm in order to solve the aircraft load optimization problem with further implementation it to the innovated load optimization model. Methods: heuristics, formalized approach, computer modeling. Results: the innovated load optimization algorithm was designed, which implies the containers groups’ assignment with minimization of loading time. Discussion: Most of studied scientific works contain various descriptions of bin packing problem’s solutions, knapsack optimization models and also outline a term of “aircraft cargo loading” as a problem of container selection, packing and cargo loading into the aircraft compartment. These models are concentrated on separate features, whereas the real load optimization problem is inextricably linked with aircraft handling and operations. This innovated load optimization model consists in decomposing the loading problem and also implementation of a new priority load planning algorithm. The following algorithm refers the predefined Unit Load Devices’ assignment in the aircraft cargo compartment in priority order to unload them according to data’s documentation without exceeding weight and balance constraints and with loading time reduction and consequently cutting handling and operation costs.